A sufficiency threshold is not a harm principle: A better alternative to best interests for overriding parental decisions. (9th September 2020) - Saunders, Ben
Abstract: Douglas Diekema influentially argues that interference with parental decisions is not in fact guided by the child's best interests, but rather by a more permissive standard, which he calls the harm principle. This article first seeks to clarify this alternative position and defend it against certain existing criticisms, before offering a new criticism and alternative. This 'harm principle' has been criticized for (i) lack of adequate moral grounding, and (ii) being as indeterminate as the best interest standard that it seeks to replace. I argue that these are not serious problems. I take Diekema's negative point to be right—our actual standard for intervention is not literally the best interests of the child—but I disagree with his proposed replacement. First, Diekema's proposed harm threshold should be more carefully distinguished from Mill's harm principle. Second, there is no reason to assume that the standard for permissible intervention coincides with the threshold for harm (or serious harm). Thus, I propose that the best alternative to the best interests standard is not a harm principle, but rather a sufficiency threshold between adequate (or 'good enough') and inadequate (or 'substandard') parenting.